2021
DOI: 10.1039/d1mh00565k
|View full text |Cite
|
Sign up to set email alerts
|

Nanofiber fabric based ion-gradient-enhanced moist-electric generator with a sustained voltage output of 1.1 volts

Abstract: Moisture-enabled electric generation as an emerging new energy-harvesting technology is one of the most fascinating and promising candidates for supplying renewable and clean power. However, existing moist-electric generators (MEGs) can...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
64
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(68 citation statements)
references
References 27 publications
0
64
0
4
Order By: Relevance
“…So far, a lot of work has been carried out on the developing and research of TMSs to improve the sensing performance of the devices, such as sensitivity, response range, response time, stability, etc., because these properties determine the practical application capabilities of the sensors [75]. Sensing performance can be improved by introducing special geometric structures, such as microarrays [76,77], microcracks [78], micropatterns [79,80], pleated structures [81,82], porous structures [83,84], spiral structures [85,86], etc. The innovation of materials is also a major key point to improve the sensing performance.…”
Section: Performancementioning
confidence: 99%
“…So far, a lot of work has been carried out on the developing and research of TMSs to improve the sensing performance of the devices, such as sensitivity, response range, response time, stability, etc., because these properties determine the practical application capabilities of the sensors [75]. Sensing performance can be improved by introducing special geometric structures, such as microarrays [76,77], microcracks [78], micropatterns [79,80], pleated structures [81,82], porous structures [83,84], spiral structures [85,86], etc. The innovation of materials is also a major key point to improve the sensing performance.…”
Section: Performancementioning
confidence: 99%
“…Recent progress has been focused on hybrids of graphene derivatives/polyelectrolytes with different polymers to improve MEGs. [24][25][26][27] Here, we propose a new design to harvest the energy of moisture flow using an ionic polymer-hydrogel-carbon composite (IPHC) (Fig. 1A).…”
Section: Introductionmentioning
confidence: 99%
“…Recent progress has been focused on hybrids of graphene derivatives/polyelectrolytes with different polymers to improve MEGs. 24–27…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is particularly important to develop a self-powered sensing system that can collect energy from the living environment or the human body instead of depending on an external power supply. 14−20 Recently, energy harvesters such as thermoelectric devices, 21,22 moist-electric generators, 23,24 triboelectric nanogenerators, 25 and piezoelectric nanogenerators 26 have been developed to enable the sensing system to be self-powered. Among them, thermoelectric devices that can directly convert low-grade thermal energy into electrical energy, have been considered as one of the best candidates as the power source for self-powered sensors since the temperature gradients are ubiquitous in nature.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, energy harvesters such as thermoelectric devices, , moist-electric generators, , triboelectric nanogenerators, and piezoelectric nanogenerators have been developed to enable the sensing system to be self-powered. Among them, thermoelectric devices that can directly convert low-grade thermal energy into electrical energy, have been considered as one of the best candidates as the power source for self-powered sensors since the temperature gradients are ubiquitous in nature. − At present, many researches on thermoelectric-based self-powered sensors have been carried out. − Lee et al reported a composite thermoelectric material composed of poly­(3,4-ethylenedioxythiophene):poly­(styrene sulfonic acid) (PEDOT:PSS) and zinc oxide (ZnO) particles.…”
Section: Introductionmentioning
confidence: 99%